Optimizing nutrient removal and biomass production of the Algal Turf Scrubber (ATS) under variable cultivation conditions by using Response Surface Methodology - Gan, Xinyu; Klose, Holger; Reinecke, Diana (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, we investigated and optimized the nutrient remediation efficiency of a simple low-cost algal biofilm reactor, the Algal Turf Scrubber (ATS), for wastewater treatment. We studied the combined effects of the three cultivation variables total inorganic carbon (TIC), nitrogen to phosphorous ratio (N:P), and light intensity. The ATS nutrient-removal efficiency and biomass productivity were analyzed according to the response surface methodology (RSM). The maximum removal rates of total P and N were 8.3 and 19.1 mg L-1 d-1, respectively. Up to 99 and 100% of total P and N were removed, within 7 days. Simultaneously, the dissolved oxygen (DO) concentration and pH value of the medium increased. The optimal growth conditions for simultaneous maximum P- and N-removal, and biomass productivity were identified. Our RSM-based optimization results provide new insights into the combined effect of nutrient- and light availability on the ATS remediation efficiency and biomass productivity.